Investigating the Relationships between COVID-19 Quality of Life, Loneliness, Happiness, and Internet Addiction among K-12 Teachers and School Administrators-A Structural Equation Modeling Approach - Karakose, Turgut; Ozdemir, Tuncay Yavuz; Papadakis, Stamatios; Yirci, Ramazan; Ozkayran, Secil Eda; Polat, Hakan (Mdpi, 2022)
It is well acknowledged that the roles of both school administrators and teachers have changed due to the global education crisis caused by COVID-19. During this challenging and critical period, it is essential to investigate how those working in the education sector who undertake strategic tasks for sustainable education are affected by the new conditions brought about by the COVID-19 pandemic. This study investigates the interrelationships between COVID-19 quality of life, loneliness, happiness, and Internet addiction. The research was designed according to the relational survey model, was conducted with 432 school administrators and teachers working in K-12 schools. The research data was collected through online questionnaires, and structural equation modelling (SEM) was used to test and analyze proposed hypotheses. The study's results revealed a positive relationship between the COVID-19 related quality of life and loneliness, and that loneliness significantly positively predicts Internet addiction. In this context, due to the impact of COVID-19 on the life quality, the participants' loneliness levels significantly increased, and this increase in loneliness caused them to become addicted to using the Internet. Interestingly, it was also determined that a positive relationship exists between loneliness and happiness and that as the loneliness of individuals increased, their level of happiness also increased. In many studies conducted prior to the COVID-19 pandemic, a negative relationship was revealed between loneliness and happiness. In the current study conducted during the pandemic, the relationship between the two variables was positive. SEM results revealed that COVID-19 directly affects the quality of life, Internet addiction, loneliness, and happiness of school administrators and teachers. Furthermore, it was determined that Internet addiction indirectly affects the relationship between loneliness and happiness.
Keywords: COVID-19; pandemic; COVID-19 quality of life; loneliness; Internet addiction; happiness; school administrator; teacher; K-12 education; structural equation modelling